Pengaruh Model Pembelajaran Problem Based Learning Berbasis Kurikulum Merdeka terhadap Peningkatan Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas X SMA Negeri 1 Pematang Siantar Tahun Ajaran 2023/2024 - Jessi Manuella Hasugian; Dorlan Naibaho; Rawatri Sitanggang; Grecetinovitria M. Butar-Butar; Maryska Debora Silalahi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this study was to determine the positive and significant influence between the Influence of the Problem Based Learning Model Based on the Independent Curriculum on Increasing Motivation to Learn Christian Religious Education and Character Education of Class X Students of SMA Negeri 1 Pematang Siantar in the 2023/2024 Academic Year. The research method used is a quantitative method with descriptive inferential data analysis. The population is all students of class X SMA Negeri 1 Pematang Siantar who are Protestant Christians, totaling 372 people and a sample of 52 people is determined using the sample random sampling technique. Data were collected using a closed questionnaire of 44 items, namely 22 items for variable X and 22 items for variable Y. The results of the data analysis showed that there was a positive and significant influence of the Problem Based Learning Model Based on the Independent Curriculum on Increasing Motivation to Learn Christian Religious Education and Character Education of Class X Students of SMA Negeri 1 Pematang Siantar in the 2023/2024 Academic Year, as evidenced by the following data analysis: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.612> rtable (a=0,05,n=52) = 0.297. b) Significant relationship test obtained tcount value = 5.600> ttable (a=0,05,dk=n-2=50)= 2.000. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂=